Evaluating three methods to encourage mentally competent older adults to assess their driving behavior. Issue 1 (July 2015) - Uribe-Leitz, Tarsicio; Barmak, Lisa Allee; Park, Angela; Howland, Jonathan; Lee, Vonne; Lodato, Emma; Driscoll, Cassandra; Dechert, Tracey; Burke, Peter A.
<x xml:space="preserve">Abstract</x> BACKGROUND Fourteen percent (43.1 million) of the population in the United States was 65 years and older in 2012. This population is projected to reach 20% (88.5 million) by 2050. Older adults accounted for 17% of all traffic fatalities and 9% of all vehicle occupant injuries in 2012. We explored the effectiveness of three interventions to help older adults assess their current driving behaviors at a Level 1 trauma center. METHODS During 2010 to 2012, 1, 216 inpatients 70 years and older admitted for surgical and medical services were screened for eligibility, and 120 were enrolled. Participants completed a driving assessment and preintervention questionnaires and were subsequently randomized to one of the following interventions: (1) brief negotiated interview plus an educational kit by the American Automobile Association about older driving plus an accompanying list of Web-based resources for older adult drivers; (2) American Automobile Association document and a list of Web-based resources; (3) online referral sheet of the list of Web-based resources only. A 3-month postintervention follow-up questionnaire was administered over the telephone to measure changes in (1) driving-related knowledge, attitudes, and beliefs as well as (2) driving-related behaviors and intended behaviors. RESULTS A total of 113 randomized patients were included in the analysis. The mean (SD) age was 76.8 (5.23) years; majority of patients were white (64%), followed by black African American (33%); and 51% were males and 49% were females. Multivariate analysis showed that older adults' driving knowledge, attitudes, and beliefs (p < 0.0001, R2 = 0.37) as well as behaviors and intentions (p < 0.0001, R2 = 0.27) toward driving were positively correlated, controlling for other predictors in the model. Intervention assignment did not affect changes in outcomes, although outcomes improved across experimental conditions. CONCLUSION Our pilot study suggests that older adults are likely to make changes in their driving behavior on the basis of minimal hospital-based intervention.